Evaluation of robotic versus open partial pancreatoduodenectomy: study protocol for a randomised controlled pilot trial (EUROPA, DRKS00020407) - Klotz, Rosa; Dörr-Harim, Colette; Bruckner, Thomas; Knebel, Phillip; Diener, Markus K.; Hackert, Thilo; Mihaljevic, André Leopold (Trials, 2021)
Partial pancreatoduodenectomy (PD) is the indicated surgical procedure for a wide range of benign and malignant diseases of the pancreatic head and distal bile duct and offers the only potential cure for pancreatic head cancer. The current gold standard, open PD (OPD) performed via laparotomy, is associated with morbidity in around 40% of cases, even at specialised centres. Robotic PD (RPD) might offer a viable alternative to OPD and has been shown to be feasible. Encouraging perioperative results have been reported for RPD in a number of small, non-randomised studies. However, since those studies showed a considerable risk of bias, a thorough comparison of RPD with OPD is warranted.
Gesehen am 31.03.2021